The Export Performance in Major Ports of India Through Containers by Custom House Agents - Paul Sundar Kirubakaran, J. (Prabandhan: Indian Journal of Management, 2010)
Containerization started in India in the year 1973 in a limited way with the creation of short-term container handling facilities at Mumbai Port Trust (MbPT) and Cochin Port Trust (CoPT). Since then, the container traffic has been recording remarkable growth particularly since 1992-1993, in tune with the growing use of containers for all types of cargo in the international trade. The port operations start with the ship reaching the port area. The ship has to call upon the port where it wants to dock, to get the permission to anchor on the port. The ship will get the permission only on submission of the Import General Manifest (IGM) to the customs (through the port authorities). IGM is the list of material which will be unloaded at the said port with details like the loading port, consignor, consignee, quantity, etc.